ANALISIS PENGARUH CAR, NPL, LDR, NIM, DAN BOPO TERHADAP ROA DENGAN GCG SEBAGAI VARIABEL KONTROL (Studi Pada Bank Umum Go Public di Indonesia Periode 2009-2013) - Rahmawati, Agustania; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to determine financial ratios commercial Bank Go Public to profitability with control variables of Good Corporate Governance (GCG).Â Â Financial ratios are proxied by CAR, NPL, LDR, NIM, and BOPO, and Profitability is proxied by ROA as a measure of the amount of profit generated. while GCG control variable is proxied by the audit committee, independent directors, institutional ownership and managerial ownership.The sample in this study is a commercial were bank go public listed in Stock Exchange (the Indonesia Stock Exchange) in the 2009-2013 period. The number used were 12 banks were taken by purposive sampling. The methods of analysis of this research using multiple linear regression with SPSS 20 Program.The results of this research show that CAR had positive but not significant effect to ROA, NPL and LDR had negative and insignificant effect to ROA, NIM had positive and significant effect to ROA, BOPO had significant negative effect to ROA, while the audit committee, independent directors, institutional ownership and ownership managerial had no effect to ROA.